2018
DOI: 10.1136/emermed-2018-207502
|View full text |Cite
|
Sign up to set email alerts
|

The association between systolic blood pressure and in-hospital mortality in older emergency department patients who are hospitalised with a suspected infection

Abstract: In older ED patients hospitalised with a suspected infection, we found an inverse linear association between SBP and case-mix-adjusted in-hospital mortality. Our data suggest that the commonly used threshold for hypotension is not clinically meaningful for risk stratification of older ED patients with a suspected infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Significant hypotension was defined as a systolic blood pressure of less than 100mmHg based on clinical data showing an increased mortality below this level and consensus guidelines from the European Society of Intensive Care Medicine. [19][20][21] The total number of blood pressure recordings taken during admission, prior to palliation, and the number of readings with a systolic value of less than 100mmHg were recorded. The proportion of hypotensive recordings compared to the total was calculated from this.…”
Section: Hypotensionmentioning
confidence: 99%
“…Significant hypotension was defined as a systolic blood pressure of less than 100mmHg based on clinical data showing an increased mortality below this level and consensus guidelines from the European Society of Intensive Care Medicine. [19][20][21] The total number of blood pressure recordings taken during admission, prior to palliation, and the number of readings with a systolic value of less than 100mmHg were recorded. The proportion of hypotensive recordings compared to the total was calculated from this.…”
Section: Hypotensionmentioning
confidence: 99%
“…Many risk stratification tools, such as the Systemic Inflammatory Response Syndrome ( SIRS), Quick Sequential Organ Failure Assessment (qSOFA) and CURB-65 scores,2 5–8 specify a single cut-off (or threshold) for each of the commonly measured vital signs, suggesting that one cut-off may discriminate between good and bad prognosis. However, recent studies in patients with traumatic brain injury and sepsis showed that prognosis linearly worsened with decreasing systolic blood pressure (SBP), without an identifiable single threshold 9 10. Similarly, linear or U-shaped instead of dichotomous associations may exist for other vital signs used in ED risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…A study by a group from the Netherlands suggests that patients above the age of 70 with suspected infection experience under-rescucitation, and this was correlated to increased mortality [27]. An inverse correlation between mortality and initial systolic blood pressure (SBP) was noted in the same age group at SBPs of 100-140mm Hg [28]. This is somewhat contrary to a study of mostly geriatric patients with sepsis who received early resuscitation upon paramedic contact that found mortality benefit was largely limited to patients with SBP below 100 mmHg [14].…”
Section: Discussionmentioning
confidence: 99%